The Impact of Grice Maxims Infringement in Adventure of Tintin Towards Communication Purposes - Fitriyani, Atika; Mujiyanto, Januarius; Suwandi, Suwandi (English Education Journal, 2020)
Communication is one of the crucial tools for life which without communication people can not interact with others. In order to have a good communication, people must obey the maxims. Maxim is a principle proposed by the philosopher Paul Grice whereby those involved in communication assume that both parties will normally seek to cooperate with each other to establish agreed meaning. The aim of this study is to find out the infringement maxim in the story of The Adventure of Tintin and to know the impact of infringement maxim in communication purposes. In obtaining the data, the researcher used descriptive qualitative to find out the out the infringement maxims among the caharcters. The object of this study is the dialogue among the characters of The Adventure of Tintin which infringe Grice’s maxim. The results of this research are the most of the characters in the dialogue infringe the maxim of quality in order to entertain the readers. The researcher found out 30 data for the infringement of Qualitative maxim, 27 data for the infringement of Quantitative maxim, 19 data for the infringement of maxim of Manner, and 29 data for the infringement of maxim of Relevance.